Role of the thymus in spontaneous development of a multi-organ autoimmune disease in human immune system mice. Issue 119 (May 2021) - Khosravi-Maharlooei, Mohsen; Li, HaoWei; Hoelzl, Markus; Zhao, Guiling; Ruiz, Amanda; Misra, Aditya; Li, Yang; Teteloshvili, Nato; Nauman, Grace; Danzl, Nichole; Ding, Xiaolan; Pinker, Elisha Y.; et al.
Abstract: We evaluated the role of the thymus in development of multi-organ autoimmunity in human immune system (HIS) mice. T cells were essential for disease development and the same T cell clones with varying phenotypes infiltrated multiple tissues. De novo -generated hematopoietic stem cell (HSC)-derived T cells were the major disease drivers, though thymocytes pre-existing in grafted human thymi contributed if not first depleted. HIS mice with a native mouse thymus developed disease earlier than thymectomized mice with a thymocyte-depleted human thymus graft. Defective structure in the native mouse thymus was associated with impaired negative selection of thymocytes expressing a transgenic TCR recognizing a self-antigen. Disease developed without direct recognition of antigens on recipient mouse MHC. While human thymus grafts had normal structure and negative selection, failure to tolerize human T cells recognizing mouse antigens presented on HLA molecules may explain eventual disease development. These new insights have implications for human autoimmunity and suggest methods of avoiding autoimmunity in next-generation HIS mice. Highlights: T cells are essential for development of multi-organ autoimmunity in humanized mice. Macrophages and De novo -generated T cells were the major disease drivers. Defective structure and impaired selection of thymocytes in the NSG mouse thymus. Lower regulatory T cells in native mouse thymus compared to grafted human thymus. Disease developed without direct recognition of antigens on recipient mouse MHC.